Etch Defect Characterization and Reduction in Hard-Mask-Based Al Interconnect Etching. (23rd September 2008) - Lee, Hong-Ji; Hung, Che-Lun; Leng, Chia-Hao; Lian, Nan-Tzu; Young, Ling-Wu; Yang, Tahone; Chen, Kuang-Chao; Lu, Chih-Yuan
Abstract : This paper identifies the defect adders, for example, post hard-mask etch residue, post metal etch residue, and blocked etch metal island and investigates the removal characteristics of these defects within the oxide-masked Al etching process sequence. Post hard-mask etch residue containing C atom is related to the hardening of photoresist after the conventional post-RIE ashing at275 ∘ C . An in situO 2 -based plasma ashing on RIE etcher was developed to prevent the photoresist hardening from the high-ashing temperature; followed wet stripping could successfully eliminate such hardened polymeric residue. Post metal etch residue was caused from the attack of the Al sidewall by Cl atoms, and too muchCHF 3 addition in the Al main etch step passivated the surface of Al resulting in poor capability to remove the Al-containing residue. The lower addition ofCHF 3 in the Al main etch step would benefit from the residue removal. One possibility of blocked etch metal island creating was due to the micromasking formed on the opening of TiN during the hard-mask patterning. We report that an additional TiN surface pretreatment with the Ar/CHF 3 /N 2 plasmas could reduce the impact of the micromasking residues on blocked metal etch.